Púrpura trombocitopênica imunológica crônica e infecção pelo Helicobacter pylori : resposta plaquetária ao tratamento de erradicação da bactéria - Barbosa, Alzira Maria de Castro (2015)
The Chronic Immune Thrombocytopenic Purpura (ITPc) is a condition caused by autoimmune response resulting awareness of platelets by self antiplatelet antibodies, causing lysis of platelets. Infection with H. pylori has been shown to likely factor for the development of PTIc, with possible platelet response relationship in PTIc after treatment of bacterial eradication. The objective was to evaluate possible effects of eradication of Helicobacter pylori in the number of platelets of patients with PTIC patients at the University Hospital Walter Cantídio. Were invited to participate in the study 29 patients with PTIc, 15 remained and all were treated for H. pylori and were followed for a period of 6 months to a year for clinical evaluation and platelet count. All patients underwent endoscopy for diagnosis of infection and, after treatment, held breath test to confirm eradication. PCR was performed for the presence of H. pylori cagA gene. Of the 15 patients 01 (6.6%) were male and 14 (93.3%) were female, the mean age was 47.7 years (27-68), the mean disease duration was 7.43 years (1-25). After the treatment, 13 patients (86.7%) eradicated H. pylori 04 (30.7%) had clinical response; and 03 (75.0%) complete response and 01 (25.0%) partial response to PTIc. It was possible to evaluate the presence of H. pylori CagA gene in 09 patients strains, 06 of these (54.5%) had CagA-positive strains. Of the 04 patients of the group who responded to treatment, 03 (75.0%) were cagA-positive. The treatment for eradication of Helicobacter pylori increased the number of platelets in 30% of patients with PTIc after six months of follow-up of these patients.